2021
DOI: 10.3390/cells10092468
|View full text |Cite
|
Sign up to set email alerts
|

An Autophagy Modulator Peptide Prevents Lung Function Decrease and Corrects Established Inflammation in Murine Models of Airway Allergy

Abstract: The involvement of autophagy and its dysfunction in asthma is still poorly documented. By using a murine model of chronic house dust mite (HDM)-induced airway inflammation, we tested the expression of several autophagy markers in the lung and spleen of asthma-like animals. Compared to control mice, in HDM-sensitized and challenged mice, the expression of sequestosome-1/p62, a multifunctional adaptor protein that plays an important role in the autophagy machinery, was raised in the splenocytes. In contrast, its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 63 publications
(100 reference statements)
1
14
0
Order By: Relevance
“…Autophagy is a very dynamic compartmentalized process; it can be increased in certain organs and tissues but decreased in other organs in the same subject. This differential activation has been described in several models of chronic inflammation and autoimmune diseases, for example in murine models of Sjögren’s syndrome [ 303 ], chronic inflammatory demyelinating polyneuropathy [ 304 ] and chronic house dust mite-induced airway inflammation [ 305 ]. With regard to neurons, as indicated above, autophagy is even more complex, with specific stages of the pathway occurring in distinct subcellular compartments.…”
Section: Awaiting Satisfactory Answers—future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Autophagy is a very dynamic compartmentalized process; it can be increased in certain organs and tissues but decreased in other organs in the same subject. This differential activation has been described in several models of chronic inflammation and autoimmune diseases, for example in murine models of Sjögren’s syndrome [ 303 ], chronic inflammatory demyelinating polyneuropathy [ 304 ] and chronic house dust mite-induced airway inflammation [ 305 ]. With regard to neurons, as indicated above, autophagy is even more complex, with specific stages of the pathway occurring in distinct subcellular compartments.…”
Section: Awaiting Satisfactory Answers—future Researchmentioning
confidence: 99%
“…As a consequence, treating an individual with a compound to induce or inhibit autophagy can have a range of individual effects. Due to this variety of effects, treating a subject with an inhibitor can restore abnormally weak levels of autophagic activity in another tissue, as illustrated by the effect of the CMA-modulator peptide P140 [ 303 , 304 , 305 ]. P140 that targets CMA and probably indirectly macroautophagy, has shown correcting effect on altered CMA activity, but display no effect on the basal, well balanced and vital autophagy process.…”
Section: Awaiting Satisfactory Answers—future Researchmentioning
confidence: 99%
“…In the HDM-induced mouse model, the administration of chloroquine alleviated airway inflammation and improved airway stenosis ( McAlinden et al, 2019 ). The intravenous injection of P140, a downregulator of CMA, attenuated ovalbumin-induced eosinophilic inflammation ( Daubeuf et al, 2021 ).…”
Section: Chronic Inflammatory Diseasesmentioning
confidence: 99%
“…Th2 cells section, upregulated Th2 differentiation was observed in autophagy-deficient mice ( Kabat et al, 2016 ). However, two studies have showed that autophagy deficiency in ovalbumin- or HDM-induced inflammation results in reduced eosinophilic inflammation ( McAlinden et al, 2019 ; Daubeuf et al, 2021 ). The results of these two studies are the opposite of those expected by Kabat et al Thus, because these two studies used whole-body autophagy-knockout mice, the specific effect of autophagy on CD4 + T cells in asthma development cannot be fully understood.…”
Section: Chronic Inflammatory Diseasesmentioning
confidence: 99%
“…Interestingly, a peptide known as P140, which is issued from the ribonucleoprotein U1-70K, also decreases expression of MHC-II molecules expressed at the surface of mouse and human B cell APCs in lupus [101][102][103][104][105]. P140 has been shown to be efficient in lupus (both in lupus-prone mice and lupus patients [106,107]) as well as in various murine models of inflammation, including primary and secondary Sjögren's syndrome [104,108], chronic house dust mite-induced airway inflammation [109], and CIDP [83]. In the same way as Quinpramine, the P140 mechanism of action involves reducing the hyperactivation of autoreactive T-cells via its effect on MHC-self peptide presentation to the receptor of autoreactive T cells.…”
Section: Antigen-presenting Cells (Apcs) and Autophagy-targeted Strategiesmentioning
confidence: 99%